Transfer of dysbiotic gut microbiota has beneficial effects on host liver metabolism - Simon Nicolas; Vincent Blasco‐Baque; Audren Fournel; Jerome Gilleron; Pascale Klopp; Aurelie Waget; Franck Ceppo; Alysson Marlin; Roshan Padmanabhan; Jason S Iacovoni; François Tercé; Patrice D Cani; et al. (Molecular Systems Biology)
Abstract Gut microbiota dysbiosis has been implicated in a variety of systemic disorders, notably metabolic diseases including obesity and impaired liver function, but the underlying mechanisms are uncertain. To investigate this question, we transferred caecal microbiota from either obese or lean mice to antibiotic‐free, conventional wild‐type mice. We found that transferring obese‐mouse gut microbiota to mice on normal chow (NC) acutely reduces markers of hepatic gluconeogenesis with decreased hepatic PEPCK activity, compared to non‐inoculated mice, a phenotypic trait blunted in conventional NOD2 KO mice. Furthermore, transferring of obese‐mouse microbiota changes both the gut microbiota and the microbiome of recipient mice. We also found that transferring obese gut microbiota to NC‐fed mice then fed with a high‐fat diet (HFD) acutely impacts hepatic metabolism and prevents HFD‐increased hepatic gluconeogenesis compared to non‐inoculated mice. Moreover, the recipient mice exhibit reduced hepatic PEPCK and G6Pase activity, fed glycaemia and adiposity. Conversely, transfer of lean‐mouse microbiota does not affect markers of hepatic gluconeogenesis. Our findings provide a new perspective on gut microbiota dysbiosis, potentially useful to better understand the aetiology of metabolic diseases.